2019
DOI: 10.5194/aab-62-393-2019
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of some Pramenka sheep breeds based on morphometric characteristics

Abstract: For the purpose of the morphometric characterization and differentiation of local sheep breeds that belong to the group of breeds called Pramenka or Zackel, two Slovenian (Bela Krajina and Istrian Pramenka) and four Montenegrin sheep breeds (Bardoka, Sjenička, Pivska Pramenka, and Zeta Žuja) were studied. The variation of morphometric measures and nine morphometric indices were analysed. Principal component analysis (PCA) was applied in order to provide an easier description of body size and shape. Regarding b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 19 publications
3
26
2
2
Order By: Relevance
“…The same researchers found the index of compactness in Cornigliese sheep breed as 84.24 in the males at the age of 0-6 months. Another study clearly showed that the breed type significantly affected IA (13). Considering the differences in terms of the fattening parameters versus characterization of breeds, the results of our study were in accordance with those of the studies in the literature.…”
Section: Fig 1 a Sample Image From Ultrasound Measurementsupporting
confidence: 90%
See 1 more Smart Citation
“…The same researchers found the index of compactness in Cornigliese sheep breed as 84.24 in the males at the age of 0-6 months. Another study clearly showed that the breed type significantly affected IA (13). Considering the differences in terms of the fattening parameters versus characterization of breeds, the results of our study were in accordance with those of the studies in the literature.…”
Section: Fig 1 a Sample Image From Ultrasound Measurementsupporting
confidence: 90%
“…Body measurement indexes. Both the ethnological and functional indexes which contribute to the breed characteristics, type, purpose, and performance were calculated as follows (4,11,13,17,19). Ultrasound measurements.…”
Section: Methodsmentioning
confidence: 99%
“…It can be suggested that Kacang goats at this location have the different of morphometric traits rather than the other regencies.. Previous studies obtained a Euclidean distance of 1.87–8.87 among Pramenka sheep from six different populations in Slovenia [ 7 ] and of 2.34–7.77 among Black Creole goats from seven diverse communities in Mexico [ 13 ]. The differences in animal management, selection, geographical area, agro-climatic conditions, and natural resources can be affected by phenotypic variation among breeds from different populations.…”
Section: Discussionmentioning
confidence: 92%
“…No studies on the morphometric characteristics of Kacang goats in Jambi Province have been published recently. Breed characterization in goats and sheep can be carried out based on body measurements and body indices [ 4 7 ]. Hence, morphometric characteristics can characterize goats and sheep from different populations [ 8 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Морфометрические параметры также применяются для косвенной оценки живой массы и направления продуктивности животных (17), отбора и подбора по экстерьеру (18). Изучение морфометрических параметров в течение длительного периода позволяет дать характеристику структуры породы и популяции, а также направления селекции за определенный промежуток времени (19).…”
unclassified